Analisis Pola Asuh Strict Parents Terhadap Anak Remaja di Lingkungan Keluarga - Aisyah Putri Adeyola; Tesa Septriani; Asti Haryati (DAWUH : Islamic Communication Journal, 2024)
The purpose of the research is to discuss parents and families who are too restrictive to their children in their own youth or may also be called Strict Parents. Because there's still a lot of parents who use a pattern of caring too strictly for their children. So the child doesn't feel comfortable at home, so the child's adolescence does not develop well because of the pattern of care given by the wrong parents. Often a child prefers silence rather than exposing his own heart to his own family. So the purpose of this study is to let us know how important it is for parents to give a good pattern of care to their children so that they become open within their own family. Data collection techniques using qualitative research with literature study methods are a series of activities similar to collection of library data, reading, recording found and collecting data by reading journals, articles, and groups of other scientific works.